2008
DOI: 10.5713/ajas.2008.70224
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II+ (HLA-DP-like) Cells in the Cow Reproductive Tract: I. Immunolocalization and Distribution of MHC Class II+ Cells in Uterus at Different Phases of the Estrous Cycle

Abstract: This study was undertaken to investigate the distribution of major histocompatibility complex class II positive (MHC II+) (HLA-DP-like) cells in the cow uterus (cervix, corpus and cornu uteri) and to compare these cells between the estrus and diestrus phases of the estrous cycle. Twenty-nine multiparous cows were used. Tissue samples from the middle of the cervix, the corpus and the right cornu were taken immediately after slaughter at the estrus or diestrus phase. Streptavidin-biotin peroxidase complex staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In that study (Eren et al 2008) mast cell-like MHC II + cells were also observed in the sections prepared from oviduct, uterus and vagina.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In that study (Eren et al 2008) mast cell-like MHC II + cells were also observed in the sections prepared from oviduct, uterus and vagina.…”
Section: Discussionmentioning
confidence: 86%
“…The distribution and heterogeneity of mast cells (Küther et al 1998;Eren et al 1999, Ozen et al 2002Vale et al 2009) and MHC II + cells (HLA-DP like, H42A) (Eren et al 2008(Eren et al , 2009 were studied previously in the genital tract of cows. In that study (Eren et al 2008) mast cell-like MHC II + cells were also observed in the sections prepared from oviduct, uterus and vagina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oviduct is of upmost importance for the maintenance of fertility in the cattle as is the case in all other mammals. We previously determined the immunolocalization and distribution of MHC Class II + cells in the uterus at different phases of the oestrous cycle (Eren et al., 2008). Distribution of these cells in other parts of the genital tract remained to be determined to obtain a more comprehensive picture of antigen presenting cells within the genital tract.…”
Section: Introductionmentioning
confidence: 99%